Melatonin improved the outcomes of women with ART: a systematic review and meta-analysis of randomized trials - Wu, Yilin; Huang, Wenjie; Tang, Li; Feng, Yuelin; Chen, Hongqing; Pan, Mingxin; Peng, Jingrong; Li, Chen; Wang, Huawei (Frontiers in Reproductive Health, 2025)
ObjectiveTo systematically evaluate whether the melatonin supplementation could improve the embryo development and pregnancy outcomes of infertile women undergoing assisted reproductive technologies (ART).MethodsThis systematic review and meta-analysis followed the PRISMA guidelines and was prospectively registered in PROSPERO (CRD420251003042). The randomized controlled trials (RCTs) published before March 5, 2025 are included to evaluate the efficacy of melatonin on infertile women undergoing ART. Eligible studies reported at least one embryo development or pregnancy-related outcome. Primary outcome was clinical pregnancy rate; secondary outcomes including oocyte yield, fertilization rate, MII oocyte number, and high-quality embryo formation. Subgroup analyses were conducted based on stimulation protocols, melatonin dosage, and population characteristics. Risk of bias was assessed using the Cochrane Risk of Bias tool, and pooled effect sizes were calculated using fixed- or random-effects models depending on heterogeneity. Totally, eleven RCTs with a total of 1,481 participants were analyzed here.Data sourcesPubMed/MEDLINE, Embase, and Cochrane Library.ResultsMelatonin supplementation significantly improved clinical pregnancy rate (OR = 1.59, 95% CI: 1.22–2.07). Regarding embryo development, melatonin significantly increased the number of high-quality embryos (MD = 0.43, 95% CI: 0.07–0.79), MII oocyte (SMD=0.99, 95% CI: 0.29–1.69), and fertilization rates (OR = 1.32, 95% CI: 1.01–1.73). No significant difference was observed in oocyte yield (SMD = 0.45, 95% CI: −0.04 to 0.94). Subgroup analysis revealed enhanced clinical pregnancy outcomes with ≤3 mg/day melatonin and under GnRH-a long protocols. Moderate to high heterogeneity was observed in some secondary outcomes, with publication bias suggested for the MII oocyte outcome.ConclusionsMelatonin supplementation may improve intermediate outcomes such as fertilization, embryo quality, and clinical pregnancy rates in women undergoing ART. With a favorable safety profile, it could be a low-cost adjunct for selected patients, though standardized guidelines are lacking and large-scale RCTs are needed to clarify long-term effects.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251003042, PROSPERO CRD420251003042.